To find the association between intrapartum amniotic fluid lactate level and labour outcome - Chander, Aravind; Panicker, Seetha; Shri, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Inspite of good monitoring in labour, there are still adverse labour outcomes. There is a need for supplementary test for early prediction of prolonged labour and fetal hypoxia. This study was undertaken to find to find the association between intrapartum amniotic fluid lactate level and labour outcome. Methods: 103 antenatal patients low risk at term, who entered into active labour either spontaneously or induced between September 2012 to August 2013 were included. Amniotic fluid was collected after doing ARM and lactate level was measured. Chi square test was used to find correlation between lactate level and duration of labour, mode of delivery and Apgar score. Results: In our study, patients with duration of labour between 8-<20hours 88 % had lactate level <10mmol/l, thus intra partum amniotic fluid lactate levels had a good negative predictive value when it was compared with the duration of labour. When the mode of delivery was analysed using Chi square test there was no statistically significant correlation (p<0.825) with amniotic fluid lactate. Spearman Rank correlation was done to observe correlation between lactate levels and Apgar which showed a correlation of 0.20 with p<0.05. Conclusions: Amniotic fluid lactate levels had better correlation with duration of labour and Apgar score. The lower the amniotic fluid lactate level, the better is the Apgar at birth. Better correlation could have been observed if amniotic fluid lactate levels were repeated every 3-4 hours during active labor. However, this was not possible due to practical difficulty in collection of sample.